2017
DOI: 10.1080/00365513.2017.1355561
|View full text |Cite
|
Sign up to set email alerts
|

Urine liver fatty acid binding protein and chronic kidney disease progression

Abstract: Excretion of the tubular protein liver fatty acid binding protein (L-FABP) is a potential novel biomarker of renal dysfunction. We examined whether urine L-FABP excretion adds prognostic information to the well-established risk markers, blood pressure (BP), albumin excretion and baseline GFR, regarding progression of chronic kidney disease (CKD). In a prospective study design a cohort of 74 stage 3-4 CKD patients (age 61 ± 13 years) were included. Glomerular filtration ratio (GFR, Cr-EDTA-clearance), 24-hour a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Evaluation of the correlation between the tested markers and biochemical parameters and blood pressure values concentration in the urine correlates with the loss of renal function only in the absence of significant albuminuria. 33 Matsui et al followed 244 adult CKD patients for 3 years and confirmed that elevated urinary L-FABP concentration was associated with progression to ESRD and the incidence of severe cardiovascular events in these patients. 34 In literature, no one before conducted research on the evaluation of L-FABP in a selected group of children with cystic kidney disease, nor did anyone make comparisons between groups of children with single and multiple renal cysts.…”
Section: Discussionmentioning
confidence: 92%
“…Evaluation of the correlation between the tested markers and biochemical parameters and blood pressure values concentration in the urine correlates with the loss of renal function only in the absence of significant albuminuria. 33 Matsui et al followed 244 adult CKD patients for 3 years and confirmed that elevated urinary L-FABP concentration was associated with progression to ESRD and the incidence of severe cardiovascular events in these patients. 34 In literature, no one before conducted research on the evaluation of L-FABP in a selected group of children with cystic kidney disease, nor did anyone make comparisons between groups of children with single and multiple renal cysts.…”
Section: Discussionmentioning
confidence: 92%
“…Because L-FABP was reported as a potential marker of CKD for patients without albuminuria (16), the detection of subclinical changes using urinary L-FABP prior to the progression to CKD is important in patients taking TAF, especially in those with low body weight.…”
Section: Discussionmentioning
confidence: 99%
“…Urine albumin is currently used in diagnosis and prognosis diabetic nephropathy while urinary nephrin and L-FABP are indicators of glomerular and tubulointerstial injury that occurs in the early stages of kidney disease. Like urinary ACE2, both nephrin and L-FABP were significantly increased among normoalbuminuric patients, positively correlated with proximal tubular dysfunction and negatively associated with eGFR ( 14 , 37 , 38 ). These observations suggest that urinary ACE2 rises in early stages of diabetes and could reflect the state of kidney function, an attribute of a good diagnostic and prognostic biomarker.…”
Section: Associations Of Urinary Angiotensin Converting Enzyme 2 Withmentioning
confidence: 95%